Marketing automation in the process of communication on the B2B market - Rostek, Katarzyna; Zawistowska, Agata (Automatyzacja marketingu w procesie komunikacji na rynku B2B, 2019)
In the perspective of the ever-growing and evolving requirements of the modern customer, there is a justified need for the better, faster and highly personalized matching of marketing activities for him/her. This challenge becomes even more difficult to implement when the client is a business entity and the marketing activities concern the B2B market. The solution, or at least an alleviation of the problem, seems to be the tools of marketing automation. However their use requires specific competences of marketing employees and an awareness of the possibilities and limitations from managers. This article presents the results of a survey conducted in a group of 100 Polish B2B market companies, the purpose of which was to identify the level and scope of applicability of marketing automation tools, characterize their advancement and the typical approach to their maintenance and further development. In terms of solutions functionality, the results of this analysis were referred to the state of the American business market. The summaries prepared on the basis of the analysis results can help in mapping further research, as well as in preparing dedicated and specialized courses and training for Polish entrepreneurs
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 1 (51), s. 72-90
Keywords: marketing automation; B2B market; information technology; market analysis; development prospects; automatyzacja marketingu; rynek B2B; technologia informatyczna; analiza rynku; perspektywy rozwoju